2014
DOI: 10.1097/md.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in Member Countries of South Asian Association for Regional Cooperation (SAARC)

Abstract: Hypertension is a leading attributable risk factor for mortality in South Asia. However, a systematic review on prevalence and risk factors for hypertension in the region of the South Asian Association for Regional Cooperation (SAARC) has not carried out before.The study was conducted according to the Meta-Analysis of Observational Studies in Epidemiology Guideline. A literature search was performed with a combination of medical subject headings terms, “hypertension” and “Epidemiology/EP”. The search was suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
135
4
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 42 publications
11
135
4
6
Order By: Relevance
“…The reported prevalence varies widely from 1.21% to 32%. 11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2). According to the Bangladesh NCD Risk Factor Survey 2010 27 , the prevalence of hypertension is 17.9% in general, 18.5% in men and 17.3% in women.…”
Section: Methodsmentioning
confidence: 99%
“…The reported prevalence varies widely from 1.21% to 32%. 11,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Table 2). According to the Bangladesh NCD Risk Factor Survey 2010 27 , the prevalence of hypertension is 17.9% in general, 18.5% in men and 17.3% in women.…”
Section: Methodsmentioning
confidence: 99%
“…DM characterized by the dysfunction in the metabolic mechanisms of carbohydrates, lipids and amino acids (Kolluru et al, 2012), whereas hypertension is characterized by persistently elevated blood pressure (Konzem et al, 2002). Worldwide, there is an increasingly high prevalence of DM from 108 million in 1980 to 422 million in 2014 (Zhou et al, 2016) and the prevalence of hypertension from the latest studies reported around 25% in Pakistan (Neupane et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[1]A meta-analysis reported the prevalence of hypertension in Pakistan to be 17% based on data gathered prior to 2004. [2] More recently, World Health Organization reported that25.2% of the Pakistani population suffered from raised blood pressure in 2014. [3] Between 2000 and 2025, the prevalence of hypertension is projected to increase by 9% in men and 13% in women.…”
Section: Introductionmentioning
confidence: 99%